Psychological Fitness Is Practice For Our Psyche (Diversity Research: Journal of Analysis and Trends, 2024)
Psychological fitness is training for the soul (our psyche). We all know that our body needs sports, and our psyche needs exercise. Physical exercise improves our body, psychological exercise improves our emotional health and, as a result, our life in general. The article examines the social psychological determinants of individual involvement in fitness practices